1999
DOI: 10.1128/aem.65.4.1420-1427.1999
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Alfalfa-Nodulating Rhizobia Present in Acidic Soils of Central Argentina and Uruguay

Abstract: We describe the isolation and characterization of alfalfa-nodulating rhizobia from acid soils of different locations in Central Argentina and Uruguay. A collection of 465 isolates was assembled, and the rhizobia were characterized for acid tolerance. Growth tests revealed the existence of 15 acid-tolerant (AT) isolates which were able to grow at pH 5.0 and formed nodules in alfalfa with a low rate of nitrogen fixation. Analysis of those isolates, including partial sequencing of the genes encoding 16S rRNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 46 publications
1
44
0
1
Order By: Relevance
“…Rhizobium sp. strain LPU83, recently isolated from acid soils of Argentina, is one example of this type of bacteria [2,18]. Data presented in this manuscript show that the addition of Ca has no marked effect on the nodulation kinetics of this bacterium and that Ca treatment increases nodulation of alfalfa by more effective S. meliloti strains, supporting an old field observation [33].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Rhizobium sp. strain LPU83, recently isolated from acid soils of Argentina, is one example of this type of bacteria [2,18]. Data presented in this manuscript show that the addition of Ca has no marked effect on the nodulation kinetics of this bacterium and that Ca treatment increases nodulation of alfalfa by more effective S. meliloti strains, supporting an old field observation [33].…”
Section: Discussionsupporting
confidence: 70%
“…To the best of our knowledge, this is the first time that an alfalfa-nodulating Rhizobium with such characteristics has been described. Like S. meliloti, LPU83 displays an impaired nodulation phenotype on alfalfa plants in mildly acidic conditions (pH 5.6) [2,18]. Although this result could tempt us to speculate that alfalfa may play a role in restricting nodulation under acidic conditions, it is also possible that the limitation of nodulation observed for this rhizobial strain is correlated to a specific bacterial problem.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Twenty-four sinorhizobia strains, part of a large collection of S. meliloti isolates from Uruguayan soils [17], were analysed to determine the production of melanin. Castro et al [18] found that 62% of them produced melanin (Mel+).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%